Kringle time [videorecording (DVD)] - Elledge, Benny; Wells, Vernon, 1945-; Keegan, Alyssa; Wincott, Jeff (Gravitas Ventures, 2021)
After becoming the unlikely star of a kid's show, a public access TV station manager named Jerry grapples with the problematic legacy of his predecessor.